2007
DOI: 10.1111/j.1600-6143.2006.01598.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD45RB Monoclonal Antibody Prolongs Renal Allograft Survival in Cynomolgus Monkeys

Abstract: Previously, an anti-CD45RB monoclonal antibody (mAb) has been shown to induce murine allograft tolerance. The present study was performed to assess the ability of an anti-human CD45RB mAb to prevent rejection in a monkey MHC-mismatched kidney transplant model. The recipients were allocated into the following treatment groups: (1) isotype control IgG; (2) mouse anti-human CD45RB IgG1 (6G3); (3) human-mouse chimeric anti-CD45RB-IgG1 (C6G3-IgG1); (4) human-mouse chimeric anti-CD45RB-IgG2 (C6G3-IgG2); (5) tacrolim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…These observations led to the hypothesis that transient anti-CD45RC mAb, which depletes CD45RC + cells, could induce not only transplant tolerance, but also favor CD45RC low/-Treg generation. Tolerance induction in two different alloincompatible rat strain combinations suggests that targeting the CD45RC molecule could be superior to anti-CD45RB mAb therapy, which resulted in a significant but only moderate increase of allograft survival in animal models, along with chronic rejection (40)(41)(42)(43)(44)(45)(46). Indeed, our results suggest that anti-CD45RB mAb could target all Foxp3 + and CD8 + Tregs that express this marker (47,48).…”
Section: Discussionmentioning
confidence: 88%
“…These observations led to the hypothesis that transient anti-CD45RC mAb, which depletes CD45RC + cells, could induce not only transplant tolerance, but also favor CD45RC low/-Treg generation. Tolerance induction in two different alloincompatible rat strain combinations suggests that targeting the CD45RC molecule could be superior to anti-CD45RB mAb therapy, which resulted in a significant but only moderate increase of allograft survival in animal models, along with chronic rejection (40)(41)(42)(43)(44)(45)(46). Indeed, our results suggest that anti-CD45RB mAb could target all Foxp3 + and CD8 + Tregs that express this marker (47,48).…”
Section: Discussionmentioning
confidence: 88%
“…ATG has been shown to prolong primate graft survival (Thomas et al 1978); however, its dosing requirements, halflife, and specificity differ so significantly from that seen in humans (the species to which ATG is raised) that it is unlikely that ATG's behavior in NHPs is a satisfactory surrogate for its use in the clinic. ATG fails to induce tolerance in most models, and is thus used primarily as induction therapy followed by some form of maintenance therapy, a variety of which have been successful (Hirshberg et al 2003;Liu et al 2007). However, a study by Haanstra et al (2006) found that ATG combined with costimulation blockade shortened the time to rejection, possibly owing to decreased intragraft inhibitory molecules.…”
Section: Depletionmentioning
confidence: 99%
“…However, use of a nondepleting antibody, OKT4A, only modestly prolonged graft survival (Cosimi et al 1990;Wee et al 1992;Mourad et al 1998). Depletion based on another potential target, CD45RB, has been shown to prolong graft survival in cynomolgus macaques (Chen et al 2007). B cells have also been targeted in depletional studies, with the agent rituximab showing prolongation of graft survival in primate islet (Liu et al 2007) and cardiac models (Kelishadi et al 2010).…”
Section: Depletionmentioning
confidence: 99%
“…24 The underlying mechanism remains largely unclear. Based on the hypothesis that the Ab might influence the activity of the enzyme, we performed an in vitro phosphatase assay to investigate the action of anti-CD45RB mAb (6G3) on the enzymatic activity of CD45.…”
Section: Anti-cd45rb Ab Increases Cd45 Phosphatase Activity In Restinmentioning
confidence: 99%
“…Indeed, antibodies (Abs) to CD45 have been effective in preventing rejection of transplants in several different animal models. [20][21][22][23] We have reported earlier that a mouse anti-human CD45RB Ab (6G3) that also recognizes monkey CD45RB has similar effects on monkey and human cells in vitro and also prevents rejection in an allogeneic nonhuman primate renal transplantation model, 24 although the molecular mechanism behind this action is unclear. This consideration prompted us to directly assess the effects of antihuman CD45RB Ab (6G3) treatment on CD45 enzymatic activity, and we observed direct stimulation of CD45 tyrosine phosphatase activity.…”
Section: Introductionmentioning
confidence: 99%